Runaway electron mitigation with supersonic molecular beam injection (SMBI) in ADITYA-U tokamak. (10th December 2020) - Banerjee, Santanu; Singh, K.; Raj, H.; Arambhadiya, B.; George, Siju; Jadeja, K.A.; Singh, Amit K.; Edappala, Praveenlal; Bisai, N.; Ghosh, J.; Manchanda, R.; Chowdhuri, M.B.; et al.
Abstract: The generation and subsequent loss of runaway electrons (REs) during the operation sequence in a tokamak is a potent threat to the plasma-facing components and the interface of actively cooled parts. Control and mitigation of REs are of prime importance to the safe operation and machine health of a fusion device. A supersonic molecular beam injection (SMBI) system has been installed in the ADITYA-U tokamak to explore the effects of the high Mach number molecular beam on the REs and ways to mitigate the REs. In the majority of discharges in which SMBI has been injected, a burst in hard x-rays has been observed accompanying the SMBI pulse, indicating significant RE loss. This is followed by a long RE-mitigated phase in the discharge. The most plausible explanation of the mitigation of REs is minor disruption caused by SMBI. This in turn triggers field line stochastization and subsequent rapid RE loss. Finally, this leads to reorganization of the flux surfaces, resulting in bigger islands with the potential of trapping any surviving RE fraction.